2000
DOI: 10.1046/j.1432-1327.2000.01434.x
|View full text |Cite
|
Sign up to set email alerts
|

Zymogen activation in the streptokinase–plasminogen complex

Abstract: Plasminogen (Plgn) is usually activated by proteolysis of the Arg561±Val562 bond. The amino group of Val562 forms a salt-bridge with Asp740, which triggers a conformational change producing the active protease plasmin (Pm). In contrast, streptokinase (SK) binds to Plgn to produce an initial inactive complex (SK´Plgn) which subsequently rearranges to an active complex (SK´Plgn*) although the Arg561±Val562 bond remains intact. Therefore another residue must substitute for the amino group of Val562 and provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…Incubation of peptides containing amino acids 1-59 of SK with inactive deletion mutants lacking these residues restores PA activity (8,9,13). Deletion of Ile 1 of SK markedly inhibits its capacity to induce an active site in plasminogen, which supports the hypothesis that establishment of a salt bridge between Ile 1 of SK and Asp 740 of plasminogen is necessary for SK to induce an active site in plasminogen by a nonproteolytic mechanism (11,14). Residues 1-59 also appear to play an important role in determining the capacity of SK to efficiently activate plasminogen in the absence of fibrin, a property that distinguishes SK from tissue-type plasminogen activator.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Incubation of peptides containing amino acids 1-59 of SK with inactive deletion mutants lacking these residues restores PA activity (8,9,13). Deletion of Ile 1 of SK markedly inhibits its capacity to induce an active site in plasminogen, which supports the hypothesis that establishment of a salt bridge between Ile 1 of SK and Asp 740 of plasminogen is necessary for SK to induce an active site in plasminogen by a nonproteolytic mechanism (11,14). Residues 1-59 also appear to play an important role in determining the capacity of SK to efficiently activate plasminogen in the absence of fibrin, a property that distinguishes SK from tissue-type plasminogen activator.…”
mentioning
confidence: 60%
“…The experiment was performed three times with similar results. mation by a nonproteolytic mechanism (14). However, complexes of plasmin and SKs harboring mutations between positions 18 -24 were severely defective in PA activity, whereas complexes of SK I1A or SK-(2-414) and plasmin exhibited normal PA activity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies demonstrating a critical role of the N terminus of SK in conformational activation support the "molecular sexuality" mechanism (34,56,57). In this mechanism, insertion of the SK N terminus into the N-terminal binding cleft in the Pg catalytic domain and salt bridge formation with Asp 194 (chymotrypsin numbering) triggers the activating conformational change.…”
Section: Discussionmentioning
confidence: 95%
“…Although SUPA could not generate an active site in h-Pg, the b-plasmin⅐SUPA complex (12). Mutagenesis studies aimed at identifying the counterion have indicated that Ile 1 is required for nonproteolytic activation of Pg, while Lys 698 appears to be required for normal binding interactions during the formation of the initial SK⅐Pg complex (12,31). The conservation of the NH 2 -terminal motif (Ile-Xxx-Gly) between SUPA and all other reported SKs underlines the importance of this residue (12).…”
Section: Discussionmentioning
confidence: 99%